Democracy in liberalism and neoliberalism: The case of Popper and Hayek - Jakob Kapeller; Stephan Pühringer (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2012)
This paper shows how classical liberalism differs from neoliberalism with respect to the frames, concepts and ideas used to describe and clarify the concept of democracy. In short we argue that while classical liberalism provides central principles for the design of western democratic institutions, a neoliberal understanding of democracy tends to undermine these very same principles. To illustrate this claim we look at the differences between two main proponents of the revival of liberalism in the second part of the 20th century, namely F.A. Hayek and K.R. Popper, with respect to their vision of acceptable democratic conduct. The differences between these two thinkers illustrate the loss of liberalism's rather clear concept of democracy through its transformation to neoliberalism.
Keywords: 330